2018
DOI: 10.4049/jimmunol.1701069
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Impair B Cell Responses in Lung Cancer through IL-7 and STAT5

Abstract: Myeloid-derived suppressor cells (MDSCs) are known suppressors of antitumor immunity, affecting amino acid metabolism and T cell function in the tumor microenvironment. However, it is unknown whether MDSCs regulate B cell responses during tumor progression. Using a syngeneic mouse model of lung cancer, we show reduction in percentages and absolute numbers of B cell subsets including pro-, pre-, and mature B cells in the bone marrow (BM) of tumor-bearing mice. The kinetics of this impaired B cell response corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 63 publications
5
77
0
Order By: Relevance
“…The criteria for characterizing the phenotype of MDSCs by flow cytometry are relatively defined, and immunosuppressive function is a functional standard defined for MDSCs. While MDSCs were initially described as merely T cell suppressive, emerging evidence suggests that MDSCs also interact with and modulate the function of other immune cells, particularly macrophages (Mø) [29,30], NK cells [31,32], Treg cells [33], and B cells [34]. Moreover, MDSCs, TAMs, and dendritic cells (DCs) have been reported to interact and cross-promote their immunosuppressive activities in the tumor microenvironment [35].…”
Section: Main Phenotypic and Functional Characteristics Of Mdscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for characterizing the phenotype of MDSCs by flow cytometry are relatively defined, and immunosuppressive function is a functional standard defined for MDSCs. While MDSCs were initially described as merely T cell suppressive, emerging evidence suggests that MDSCs also interact with and modulate the function of other immune cells, particularly macrophages (Mø) [29,30], NK cells [31,32], Treg cells [33], and B cells [34]. Moreover, MDSCs, TAMs, and dendritic cells (DCs) have been reported to interact and cross-promote their immunosuppressive activities in the tumor microenvironment [35].…”
Section: Main Phenotypic and Functional Characteristics Of Mdscsmentioning
confidence: 99%
“…Most of the impairments were attributable to the direct effects of MDSCs, and they were related to and seemingly mediated by a IL-7-mediated reduction in STAT5 signaling and dysfunctional B cell responses. In addition, the authors revealed that TGF-β (an MDSC-associated cytokine) was a central inhibitor of IL-7 signaling in B cells in the TIME [34].…”
Section: Stat Signaling Pathwaymentioning
confidence: 99%
“…This mechanism could exist in obese prostate cancer patients . Besides STAT3, the other STAT family members including STAT1, STAT5 and STAT6 also have significant effects on the activity and function of MDSCs . After activation by IL‐1β and IFN‐γ, STAT1 suppresses the activity of T cells by promoting the secretion of iNOS and Arg‐1 of MDSCs, while STAT6 can regulate the suppressive effects of STAT1.…”
Section: Main Functional Characteristics Of Mdscsmentioning
confidence: 99%
“…MDSC have additionally been shown to inhibit natural killer cell Fc receptor mediated functions including antibody‐dependent cellular cytotoxicity (ADCC), cytokine production, and signal transduction 29 . MDSC also impair B cell differentiation and proliferation 30 …”
Section: Mdsc In Cancermentioning
confidence: 99%
“…Use of a CCR2 antagonist recapitulated the genetic ablation results. Blocking CCL2 inhibited MDSC recruitment and delayed tumor progression in a lung cancer model, added along with a combination treatment with anti‐PD1 antibody, resulted in higher infiltration of T cells and production of interferon γ, which corresponded to an increase in survival 30,79 …”
Section: Targeting Mdsc To Improve Immunotherapy and Immunosurveillancementioning
confidence: 99%